Time in Contemporary Philosophy (Al-Farooq Journal of Sciences, 2026)
This research aims to trace the conceptual transition of the notion of time from being a quantitative physical datum measured by clocks to a subjective existential experience at the core of human being. It also seeks to demonstrate the fundamental differences between mathematical time and "lived duration" (durée) in Bergson's philosophy, explore the transformation of time into an "horizon of being" in Heidegger's work, and analyze the structure of temporal consciousness in phenomenology, reaching an examination of the implications of relativity and spacetime on contemporary philosophical and logical thought.The research utilized a descriptive-analytical approach with a comparative philosophical dimension to monitor the evolution of the concept, in addition to the phenomenological method to describe the experience of consciousness in the present moment and how the self perceives its own duration. The study relied on library research and content analysis of original philosophical texts and modern studies.The research concluded that real time is not fragmented mathematical time, but rather a continuous duration in which the past blends with the present through consciousness. The results also proved that time represents the ontological horizon of the human being (Dasein), where consciousness of the future and finitude gives existence its meaning. Furthermore, the study showed that the integration of time and space into the concept of "spacetime" has overturned the idea of absolute time, making way for a multiplicity of times and the relativity of contexts.The research recommended the necessity of transcending the dry mechanical view of time in the humanities and treating time as a living fabric that defines identity. It also called for deepening interdisciplinary studies between the philosophy of consciousness and modern physics, and integrating the existential temporal dimension into education and psychology to enhance an individual's ability to invest in their own duration, while remaining open to the ethical dimensions of time to create a more authentic and responsible life.